Analysis of Phonetic Errors in Sound Pronunciation for Eighth-Grade Students of Al-Manar Islamic High School, Prambon Nganjuk: تحليل الأخطاء الصوتية في نطق الصوت لطلاب الصف الثامن بالمدرسة المتوسطة الإسلامية المنار فرمبون عانجوك - Elyana Maula Nur Aini; Nur Khamidah (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2021)
In learning Arabic, we must recognize the letters that exist in the Arabic language; this is inseparable from the sound in the language. Sound sounds are a staple of language learning. To distinguish sounds from one another, we must practice correctly and precisely pronouncing letters. If one of the letters is wrong in pronunciation, then the meaning or meaning will also be different. Therefore, we must be careful in the pronunciation of Arabic feared there is a problem. This study discusses the error in the sound of the voice of students of Class VIII al-Manar Junior Hight School. This study aims to answer questions related to sound errors in pronunciation in students of Class VIII al-Manar Junior High School because of the occurrence of sound classes in the pronunciation of sounds; how to overcome the sound errors in students of Class VIII al-Manar Junior Hight School. This research includes a descriptive qualitative study; therefore, in the problem, researchers use the method of observation, interviews, and documentation. After the data was obtained and collected, researchers used error analysis techniques. The results of this study are as follows: 1) sound errors in the pronunciation of sounds in Class al-Manar Junior Hight School many occur in the aspect of adding and replacing errors. 2) the cause of the sound error in the pronunciation of the sound in the VIII grade students MTs al-Manar due to the lack of habituation in Reading Arabic. 3) The Teacher's effort to overcome the error of the sound of the voice in the VIII grade students of al-Manar Junior High School is to guide students uniquely.. في تعلم اللغة العربية وجب علينا أن نعرف الحروف التى تكون إحدى عناصر اللغة. لتمييز الأصوات عن بعضهم بعض، فيمبغى لنا لنتعلم كيفية بشكل صحيح، إذا يوجد الخطأ في النطق حرف واحد. فيكون معنه مختلفا. لذالك يمبغى لنا لنتجاهة نطق الحرف العربية لكي يبتعد الأخطاء. يفيض هذا البحث العلمي تحليل الأخطاء الصوتية في نطق الصوت لطلاب الصف الثامن بالمدرسة المتوسطة الإسلامية المنار. تهدف هذا البحث للإجابة على الأسئلة عن الأخطاء الصوتية في نطق الصوت لطلاب الصف الثامن بالمدرسة المتوسطة الإسلامية المنار، وعن العوامل التي تسبب الأخطاء الصوتية في نطق الصوت لطلاب الصف الثامن بالمدرسة المتوسطة الإسلامية المنار، وعن حل مشكلات الأخطاء الصوتية في نطق الصوت لطلاب الصف الثامن بالمدرسة المتوسطة الإسلامية المنار. استعمل هذا البحث بحث الكيفي الوصفي، وتستخدم الباحثة طيريق جمع البيانات نحو الملاحظة والمقابلة والثائق. بعد أداء جمع البيانات تحل الباحثة البيانات بطريقة تحليل الأخطاء.نتائج هذا البحث هي كما يلي: 1) أخطاء في نطق الصوت هذا طلاب في الصف الثامن المدرسة المتوسطة الإسلامية المنار يدل نتائج غير مميتا في ناحية الإضافة والتحريف. و من الناحية الإبدال والحذف يخطأ الطلاب نطق الصوت بشكل كثير. 2) سبب مشكلات الأخطاء الصوتية في نطق الصوت لطلاب الصف الثامن المدرسة المتوسطة الإسلامية المنار هو نقص التدريب القراءة اللغة العربية. 3) محاولة المعلمة للتغلب على الأخطاء الصوتية في نطق الصوت لطلاب الصف الثامن المدرسة المتوسطة الإسلامية المنار هي بطريقة التعلم الفردي.